Chapter La scrittura scientifica dopo la 'rivoluzione scientifica'. Tre exempla: Galilei, Darwin, Piaget - Mariani, Alessandro (Studies on Adult Learning and Education, 2022)
This paper focuses on the structure and function, as well as on the interweavings, variations and integrations of three types of scientific writing (the dialogue, the treatise, the essay) to which Italian pedagogy has focused only partially. From the reflections presented and through the examples given (Galilei, Darwin, Piaget) it emerges that, starting with the "scientific revolution," the renewal of science has also taken place with the contribution of scientific writing, which has become progressively more linear, more open, more disseminated, more dialectical, and more informative.